Investigation of differentially expressed proteins through neurofibrillary tangle maturation in Alzheimer's disease using NanoString's GeoMx Digital Spatial Profiler. (20th December 2022) - Moloney, Christina M.; Liu, Chia‐Chen; Wickland, Daniel P.; Lesser, Elizabeth R.; Kachergus, Jennifer; Van Blitterswijk, Marka M.; Graff‐Radford, Neill R.; Dickson, Dennis W.; Thompson, E. Aubrey; Murray, Melissa E.
Abstract: Background: Neurofibrillary tangles are dynamic entities with a lifespan encompassing three maturity levels: intracellular pretangles, intracellular mature tangles, and extracellular ghost tangles. Proteins are suggested to be differentially expressed throughout the tangle lifespan; however, past studies may be limited by spatial expression or number of proteins investigated. We sought to assess differences in protein expression across the tangle lifespan using GeoMx TM Digital Spatial Profiler (DSP) by NanoString, a new technology allowing for spatially derived multiplex investigation. Method: We used DSP to measure protein expression in hippocampi from Alzheimer's disease (n=6) and nondemented controls (n=2) using the "Human Neural Cell Profiling Core" and "Alzheimer's Pathology" module. Regions of interest (ROIs) were classified by the major tangle maturity level recognized by a primary fluorescent conjugated tau antibody. Protein expression was normalized to the geomean of the three housekeeping genes. The tau‐positive segment was specifically analyzed for comparisons. ANOVA was used for group‐wise comparisons and t‐test using the Benjamini‐Yekutieli adjustment for multiple tests was used for pair‐wise comparisons. Result: As expected, cytoskeletal (e.g., MAP2, Tau) and neuronal (e.g., NeuN) markers generally decreased through the neurofibrillary tangle lifespan (Figure). Markers profiled as neurodegenerative (e.g., amyloid‐β1‐42, APOE, APP) generally increased through tangle maturity levels, except for TDP‐43 which decreased. Interestingly, there was no significant difference in ubiquitin expression. Astrocytic GFAP and S100B expression was significantly increased through each maturity level. Expression of microglial‐specific markers P2RY12 and TMEM119 was significantly elevated in ghost tangles compared to mature tangles. Additional microglial/macrophage markers including Iba‐1 and CD68 were generally increased as neurofibrillary tangles matured. Interestingly, APOE expression remained low in pretangles and mature tangles before dramatically increasing in ghost tangles (Figure). Conclusion: Our findings suggest that proteins are differentially expressed throughout the tangle lifespan and the majority followed a monotonically directed pattern. Non‐monotonically directed protein patterns may reflect the death of the neuron during the ghost tangle maturity level. Future studies will test the hypothesis that the microenvironment of the hippocampus is altered with increasing vulnerability to tangle pathology.